Identification of a novel peptide targeting TIGIT to evaluate immunomodulation of 125I seed brachytherapy in HCC by near-infrared fluorescence - Zeng, Peng; Shen, Duo; Shu, Wenbin; Min, Shudan; Shu, Min; Yao, Xijuan; Wang, Yong; Chen, Rong (Frontiers in Oncology, 2023)
Introduction Hepatocellular carcinoma (HCC) has very poor prognosis due to its immunosuppressive properties. An effective measure to regulate tumor immunity is brachytherapy, which uses 125I seeds planted into tumor. T cell immune receptors with immunoglobulin and ITIM domains (TIGIT) is highly expressed in HCC. The TIGIT-targeted probe is expected to be an effective tool for indicating immunomodulation of 125I seed brachytherapy in HCC. In this study, We constructed a novel peptide targeting TIGIT to evaluate the immune regulation of 125I seed brachytherapy for HCC by near-infrared fluorescence (NIRF). Methods Expression of TIGIT by immunofluorescence (IF) and flow cytometry (FCM) in different part and different differentiated human liver cancer tissues was verified. An optical fluorescence probe (Po-12) containing a NIRF dye and TIGIT peptide was synthesized for evaluating the modulatory effect of 125I seed brachytherapy. Lymphocytes uptake by Po-12 were detected by FCM and confocal microscopy. The distribution and accumulation of Po-12 in vivo were explored by NIRF imaging in subcutaneous and orthotopic tumors. IHC and IF staining were used to verify the expression of TIGIT in the tumors. Results TIGIT was highly expressed in HCC and increased with tumor differentiation. The dye-labeled peptide (Po-12) retained a stable binding affinity for the TIGIT protein in vitro. Accumulation of fluorescence intensity (FI) increased with time extended in subcutaneous H22 tumors, and the optimal point is 1 h. TIGIT was highly expressed on lymphocytes infiltrated in tumors and could be suppressed by 125I seed brachytherapy. Accumulation of Po-12-Cy5 was increased in tumor-bearing groups while declined in 125I radiation group.